2018
DOI: 10.1093/synbio/ysy017
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a living biomaterial via bacterial surface capture of environmental molecules

Abstract: Synthetic biology holds significant potential in biomaterials science as synthetically engineered cells can produce new biomaterials, or alternately, can function as living components of new biomaterials. Here, we describe the creation of a new biomaterial that incorporates living bacterial constituents that interact with their environment using engineered surface display. We first developed a gene construct that enabled simultaneous expression of cytosolic mCherry and a surface-displayed, catalytically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…9a). 140 It has been reported that each E. coli cell expresses up to 100000 copies of OmpA, making it theoretically possible to display chimeric fusion proteins at a high density on the microbial surface. 141 The surface display of SNAP-tagged proteins enables microorganisms to covalently bind benzylguanine (BG)modified molecules in the environment, providing proof of concept for sequestering and assembling BG-functionalized molecules on the surface of the material (Figure 9b).…”
Section: Functional Modification Of Cell Surfacesmentioning
confidence: 99%
See 4 more Smart Citations
“…9a). 140 It has been reported that each E. coli cell expresses up to 100000 copies of OmpA, making it theoretically possible to display chimeric fusion proteins at a high density on the microbial surface. 141 The surface display of SNAP-tagged proteins enables microorganisms to covalently bind benzylguanine (BG)modified molecules in the environment, providing proof of concept for sequestering and assembling BG-functionalized molecules on the surface of the material (Figure 9b).…”
Section: Functional Modification Of Cell Surfacesmentioning
confidence: 99%
“…coli, such as OmpA, intimin, and HlyAc (C-terminal fragment of hemolysin-protein A). Scott et al fused OmpA with a SNAP-tag, an O 6 -alkyl guanine DNA alkyltransferase from humans, to design living materials to capture environmental molecules (Figure a) . It has been reported that each E.…”
Section: Engineering Living Materials Through the Lens Of Synthetic B...mentioning
confidence: 99%
See 3 more Smart Citations